PARTICIPATION OF HIGH-SCHOOL STUDENTS IN NANOTECHNOLOGY RESEARCH AND DIFFUSION - Souza-Filho, Moacir P. de [UNESP]; Ribeiro, Allan V.; Raminelli, Ulisses J.; Raminelli, Carla M. de P.; Silva, Fernanda Bertaco da [UNESP] (Univ Nacl Colombia, Fac Sci, 2017)
With the aim of motivating high school students to study at the university level and to provide a solid scientific initiation, the Vice-Rectory of Research of UNESP - State University of Sao Paulo, has granted three (03) scholarships of the Institutional Program for Scientific Initiation - PIBIC Junior. In 2016, a proposal to obtain three additional scholarships has been submitted. This would support the participation of new students. The project involves a collaboration between UNESP, IFSP - Federal Institute of Sao Paulo and the State School Felicio Tarabay. It is supplemented by the activities of the NANODYF International Network, which aims at the training and dissemination of nanoscience and nanotechnology. The activities of the students consist of the study of textbooks and scientific articles and the development of research activities under the mentorship of the authors, the participation in scientific events such as the ETIC - Toledo Meeting of Scientific Initiation, and visits to the IFSP. After the training, the students will present seminars and conferences to the rest of the students at the school, with the aim of contributing to the diffusion of research and applications related to nanotechnology. In addition to the students receiving the scholarships, there is a significant number of interested students who act as volunteers. In this work the interest and motivation of the students to participate in the actions of the project at the secondary school are investigated. We believe that actions such as this project may contribute greatly to the formation of citizens who are aware of current technological advances, holders of good prospects and excellent candidates for scientific careers.
Keywords: Nanoscience and Nanotechnology; interdisciplinary; Teacher Training